DEVELOPMENT OF BANANA PLANTS BIOFERTIRRIGADAS, WITH EMPHASIS ON SOIL MICROBIOTA - Saraiva, João Paulo Bezerra; Gomes, Vânia Felipe Freire; Mendes Filho, Paulo Furtado; Freitas, Emanuel Dias; Sousa, Luci Cleide Farias Soares (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2011)
- Brazil is one of the largest producers of banana (Musa sp.), Accounting on average for 10% of the total world production. From this perspective, it is possible to see the need to increase their production, and among the strategies adopted, one can anticipate the acclimatization phase, through the association of banana seedlings mycorrhizal fungi. The biofertilizers commonly refer to the effluent resulting from aerobic or anaerobic fermentation of organic products supplemented with pure or mineral products. They are used in agriculture for various purposes, and its application promotes the improvement of physical and chemical properties and stimulating biological activity.